Scotus for dunces : an introduction to the subtle doctor - Ingham, Mary Beth, 1951- (Franciscan Institute Publications, 2003)
This book is a simple guide to theological and philosophical aspects of the thought of the medieval Franciscan, John Duns Scotus. Known as the Subtle Doctor, Scotus has a reputation for intricate and technical reasoning. Ingham provides an insightful and creative introduction to his thought in this book. Philosophical and theological principles are explored with clarity and demonstrated by the use of numerous practical examples. By organizing the book around themes that are both timely and urgent, Ingham invites the reader into thoughtful reflection, encourages lively discussion, and challenges Franciscans in particular to consider choosing patterns of relationships that strive for the good and beauty in all things.